1992
DOI: 10.1152/jn.1992.67.2.411
|View full text |Cite
|
Sign up to set email alerts
|

Parallel processing of tactile information in the cerebral cortex of the cat: effect of reversible inactivation of SI on responsiveness of SII neurons

Abstract: 1. Localized cortical cooling was employed in anesthetized cats for the rapid reversible inactivation of the distal forelimb region within the primary somatosensory cortex (SI). The aim was to examine the responsiveness of individual neurons in the second somatosensory area (SII) in association with SI inactivation to evaluate the relative importance for tactile processing of the direct thalamocortical projection to SII and the indirect projection from the thalamus to SII via an intracortical path through SI. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
53
0
1

Year Published

1994
1994
2011
2011

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(62 citation statements)
references
References 0 publications
8
53
0
1
Order By: Relevance
“…Nevertheless, ablations of SI, and even areas 3a and 3b alone, totally deactivated the SII area in monkeys, implying serial processing of the somatic information [15,28]. However, recent studies by Turman et al [32] and Rowe et al (1994, personal communication) suggest that tactile input can reach SII directly from thalamus both in cats and in monkeys, and that SI may have a backround facilitatory influence on the function of SII.…”
Section: Discussionmentioning
confidence: 96%
“…Nevertheless, ablations of SI, and even areas 3a and 3b alone, totally deactivated the SII area in monkeys, implying serial processing of the somatic information [15,28]. However, recent studies by Turman et al [32] and Rowe et al (1994, personal communication) suggest that tactile input can reach SII directly from thalamus both in cats and in monkeys, and that SI may have a backround facilitatory influence on the function of SII.…”
Section: Discussionmentioning
confidence: 96%
“…Indeed, an alternative interpretation could be that the functional state of S2 is dependent on the functional state of S1, through intrinsic connections between the two areas [i.e., S1 could exert a control on the excitability of S2 neurons (Turman et al, 1992)]. Hence, the ablation of S1 could reduce the responsiveness of S2 to non-nociceptive inputs originating directly from the thalamus, by removing a background facilitatory influence of S1 on the neural activity in S2 (Turman et al, 1992). Our results, suggesting a direct processing of non-nociceptive somatosensory input from the thalamus to S2 (Fig.…”
Section: Parallel Processing Of Non-nociceptive Input In S1 and S2mentioning
confidence: 99%
“…In lower primates, several studies have shown that nonnociceptive somatosensory information is transmitted from the thalamus to both S1 and S2 via segregated thalamocortical pathways, thus indicating a parallel processing of non-nociceptive somatosensory input in S1 and S2 (Garraghty et al, 1991;Turman et al, 1992). In contrast, the processing of non-nociceptive somatosensory input in higher primates and humans remains, at present, a matter of debate Iwamura, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…From here, the information is conveyed over a parallel projection network to two principal cerebral cortical target regions, the primary and secondary somatosensory areas of the cortex (SI and SII, respectively) (Bennett et al 1980;Ferrington and Rowe 1980b;Fisher et al 1983;Mackie et al 1996;Rowe et al 1985;Turman et al 1992Turman et al , 1995Zhang et al 1996Zhang et al , 2001a. At the cortical level, a substantial decline is apparent in SI, in the tightness of phaselocking of individual responses, with phaselocking absent at vibration frequencies above ϳ100 Hz (Ferrington and Rowe 1980b;Mountcastle et al 1969), whereas within SII, individual neurons can retain phaselocked responses at vibration frequencies up to ϳ300 Hz (Ferrington and Rowe 1980b;Ghosh et al 1992;Rowe 1990;Rowe et al 1985).…”
Section: Signaling Of Vibrotactile Information At Thalamocortical Levmentioning
confidence: 99%